Answers

2016-02-15T23:26:49+05:30
P(9a-2,b) = (x,y)
A(3a+1.-3) = (x1,y1)
B(8a,5) = (x2,y2)
Ratio (m1,m2) = 3,1

x = m1*x2 + m2*x1
      ---------------------
            m1 + m2
9a-2 =3*8a +1* 3a+1
           -----------------
                  3 + 1
9a-2 = 24a + 3a + 1
            ----------------
                    4
36a - 8 = 27a + 1
36a - 27a= 1 + 8 
9a = 9
a = 9
     -----
      9
a = 1

Now,


y = m1*y2 + m2*y1
      ---------------------
            m1 + m2
-b = 3*5 + 1 * -3
       ----------------
               4
-b = 15 - 3
        --------
            4
-b = 12/4
-b = 3
b = -3

Therefore a = 1, b = -3
If Any Doubts Regarding To This Solution Plz Feel Free To Ask Or Any Other Doubt About Any Chapter Of Any Subject Plz Consult ME

1 5 1